Making Duplicate Files Using the Atari Computer and the Atariwriter and Atariwriter Plus Programs. Doc. No. 0005 - Schlenker, Richard M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
Step-by-step instructions for creating duplicate files using the Atariwriter or Atariwriter Plus word processing software are provided. An example of a standard file format for lesson plans is included. (MES)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Software; Word Processing; Atariwriter; Guides, Classroom -- Teacher; Computer Programs